SARS Coronavirus-2 variant tracing within the first Coronavirus Disease 19 clusters in northern Germany. (January 2021) - Pfefferle, Susanne; Günther, Thomas; Kobbe, Robin; Czech-Sioli, Manja; Nörz, Dominic; Santer, René; Oh, Jun; Kluge, Stefan; Oestereich, Lisa; Peldschus, Kersten; Indenbirken, Daniela; Huang, Jiabin; et al.
Abstract: Objectives: Investigation whether in depth characterization of virus variant patterns can be used for epidemiological analysis of the first severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection clusters in Hamburg, Germany. Methods: Metagenomic RNA-sequencing and amplicon-sequencing and subsequent variant calling in 25 respiratory samples from SARS-CoV-2 infected patients involved in the earliest infection clusters in Hamburg. Results: Amplikon sequencing and cluster analyses of these SARS-CoV-2 sequences allowed the identification of the first infection cluster and five non-related infection clusters occurring at the beginning of the viral entry of SARS-CoV-2 in the Hamburg metropolitan region. Viral genomics together with epidemiological analyses revealed that the index patient acquired the infection in northern Italy and transmitted it to two out of 134 contacts. Single nucleotide polymorphisms clearly distinguished the virus variants of the index and other clusters and allowed us to track in which sequences worldwide these mutations were first described. Minor variant analyses identified the transmission of intra-host variants in the index cluster and household clusters. Conclusions: SARS-CoV-2 variant tracing allows the identification of infection clusters and the follow up of infection chains occurring in the population. Furthermore, the follow up of minor viral variants in infection clusters can provide further resolution on transmission events indistinguishable at a consensus sequence level.